Dual-band circularly polarized microstrip antenna for wireless application - Jeevanandham Nijee (2013)
The dual-band circularly polarized, aperture antennas are proposed and studied using microstrip feed with L-shaped strip. The antennas consist of an aperture fed by microstrip line along with L-shaped stub. An impedance transformer is used to improve the matching of the antenna. The aperture and feeding structure along with L-shaped are fabricated on a low cost FR4 substrate.